Mycoremediation of heavy metal pollution: A review - Cazan, Bogdan; Iordache, Ovidiu-George; Mihai, Carmen; Perdum, Elena; Dinca, Laurentiu (Technium Sustainability, 2024)
Heavy metal pollution of the environment is one of the biggest issues of today’s society. Whether it affects soils or water, once introduced in the environment, heavy metals cannot be biodegraded. In agriculture, heavy metal pollution affects both the quality and the quantity of the crops. In the aquatic environment, heavy metals affects not only the aquatic life but also it affects human directly, through the contamination of the drinking water. Their presence in environment results in bioaccumulation, further affecting biological and ecological cycles. Mining activities, chemical weathering of minerals, leather and textile industry and industrial discharges are just a few examples of heavy metals pollution sources. However, some heavy metals have importance as trace elements, for the growth and development of organisms such as plants and fungi. Due to their persistence in environment, microorganisms have evolved mechanisms to tolerate heavy metals presence through adsorption or chemical reduction of metal ions. In fact, the role of fungi as decomposers in the ecosystems led to the studying of their enzymes and ability to mycoremediate heavy metals. To obtain mycoremediation of heavy metal pollution, the aim is to determinate the right fungal species to target a specific pollutant. This paper aims to review the potential of fungi to bioremediate heavy metal pollution.